Midgut malrotation presenting as duodenal obstruction in an adult: a rare entity! - Kamath, Bharat S.; Shah, Shivani K.; Nandu, Vipul V.; Roy, Arpit R. (International Journal of Research in Medical Sciences, 2025)
Intestinal malrotation is a congenital anomaly of the small bowel with an incidence of 1 in 500 live births, mostly presenting in infancy. Presentation in adults is rare. A 46 -year-old male presented with acute pain in abdomen, obstipation and bilious vomiting. The patient was vitally stable with insignificant clinical examination and normal hematological investigations. On abdominal CT, abnormal right sided small bowel loops with pulled up caecum in the midline, fibrotic bands extending from the DJ flexure towards the caecum, and Whirlpool sign relating to the superior mesenteric vein were seen. The patient was managed conservatively initially, and subsequently a Ladd’s procedure was performed. Post operative course was uneventful. Though rare after childhood, symptomatic midgut malrotation may present in adults. Thus, high index of suspicion in patients presenting with non-specific abdominal pain and recurrent bilious vomiting, allows early recognition and management of this rare cause of small bowel obstruction.